Islamic Society and State Power in Senegal - Ahmed Sheikh Bangura (International Institute of Islamic Thought, 1997)
Senegal is one of the most stable sub-Saharan African countries. Leonardo Villal6n's book, Islamic Society and State Power in Senegal, attributes that stability to the forms of religious organization provided by Senegal's unique brands of Sufism. Most Senegalese are affiliated to a marabout (Sufi leader) and are members of a Senegalese Sufi order. These orders remain the most pervasive forms of social organization. Leonardo Villal6n's work, devoted to an examination of the shape of Senegalese society, therefore focuses on its most salient feature: the forms and patterns of its religious organization. The author argues that the Senegalese Sufi orders, developed in the wake of French colonialism, provide an effective mode of social organization vis-a-vis the state. They check the hegemonic ambitions of the state and give a measure of leverage to the disciple-citizens in their dealings with it. This maraboutic system explains much of Senegal's relative success in maintaining a dynamic balance between state and society. In other words, the Sufi pattern has become the basis for the establishment of a religiously based "civil society." While this balance remains precarious, as there are conceivable factors that can disrupt it, it has thus far shielded Senegal from the instability and strife that continue to bedevil many African societies ...